From pain to meningitis: bacteria hijack nociceptors to promote meningitis - Liu, Huazhen; Kong, Xingxing; Zeng, Yuqin; Chen, Jinyun; Chen, Zhanpeng; Liu, Lanlan; Ma, Quan; Liu, Xuhui; Lu, Shuihua (Frontiers in Immunology, 2025)
Bacterial meningitis is a severe and life-threatening infection of the central nervous system (CNS), primarily caused by Streptococcus pneumoniae and Neisseria meningitidis. This condition carries a high risk of mortality and severe neurological sequelae, such as cognitive impairment and epilepsy. Pain, a central feature of meningitis, results from the activation of nociceptor sensory neurons by inflammatory mediators or bacterial toxins. These nociceptors, abundantly present in the meninges, trigger neuroimmune signaling pathways that influence the host immune response. However, the mechanisms by which bacteria hijack these nociceptors to promote CNS invasion and exacerbate the disease remain poorly understood. This review examines the interactions between bacteria and meningeal nociceptors, focusing on their direct and indirect activation via ion channels, such as transient receptor potential vanilloid-1 (TRPV1) and transient receptor potential ankyrin 1 (TRPA1), or through the release of neuropeptides like calcitonin gene-related peptide (CGRP). These interactions suppress immune defenses by inhibiting macrophage activity and neutrophil recruitment, thus facilitating bacterial survival and invasion of the CNS. Understanding this neuroimmune axis may open potential therapeutic targets for treating bacterial meningitis by enhancing host defenses and mitigating pain. Further research using advanced methodologies is essential to clarify the role of nociceptor-mediated immune modulation in this disease.